L’atto reale e la genesi del soggetto nella psicoanalisi di Jacques Lacan - Lattuada, Alessandro (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
This paper proposes to analyze the genesis of the subject in Lacanian psychoanalysis. Through Freudian concepts as the principle of pleasure and the Thing (das Ding), Lacan elaborates an original theory of subjectivation, based on the dialectical relationship between the pursuit of individual pleasures (pleasure principle) and the needs of society (reality principle). In this regard, Žižek’s interpretation is extremely significant; he finds in Lacan a guide for the contemporary world: a political philosophy founded on the Ethics of psychoanalysis able to identify the subject who can face the empire of economic globalism. The problem of analysis, from its medical and individual essence, expands itself to the point of investing the problem of society - and therefore, it insinuates itself to the full right in the field of philosophical and political questions. Lacan, tracing and implementing the Freudian path, appears - according to Žižek’s interpretation - as an essential resource to understand the role of the subject in the contemporary world.